Application of Rice Husk Ash as a Partial Substitute for Fine Aggregate in Concrete - , Ritesh Jain; , Satinder Kaur Khattra (Archives of Current Research International, 2025)
Throughout the building era, concrete—a composite material made by humans—was mostly utilized as a binding element for structures. One of the industries in India that is growing the fastest is the building sector. Traditional building resources like bricks, cement, sand, and wood are becoming more and more limited as a result of the rapid rate of growth and the growing demand for buildings. Researchers have been forced to create a range of novel and inventive building materials due to the requirement for high-quality building materials to replace conventional ones as well as the necessity for fairly priced and long-lasting materials for affordable housing. In order to optimize the use of locally available resources, this study examined the effects of replacing fine aggregate with rice husk in terms of weight on the workability, bulk density, and compressive strength of concrete. In M-20 grades of concrete, the suitability of using rice husk at 5%, 10%, 15%, 20%, and 25% as a partial substitute for fine aggregate was also evaluated. The concrete's compressive strength is influenced by the kind and amount of curing that is done before to the test. Experiments show that after 28 days, the strength is higher than after 7 days. Strength levels are higher for M20 with 10% replacement than for M20 with 15% replacement. This demonstrates that the strength value falls as the proportion rises.